2012
DOI: 10.1111/jcmm.12007
|View full text |Cite
|
Sign up to set email alerts
|

Identity of tendon stem cells – how much do we know?

Abstract: Tendon stem cells are multi-potent adult stem cells with broad differentiation plasticity that render them of great importance in cell-based therapies for the repair of tendons. We called them tendon-derived stem cells (TDSCs) to indicate the tissue origin from which the stem cells were isolated in vitro. Based on the work of other sources of MSCs and specific work on TDSCs, some properties of TDSCs have been characterized / implicated in vitro. Despite these findings, tendon stem cells remained controversial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 74 publications
2
57
0
2
Order By: Relevance
“…Moreover, since the IdU label was lost during cell proliferation, it could only be used to trace the early events after tissue injury. The use of other tendon stem cell tracking methods should be considered if investigators are interested in the mid-to-late events after injury [45]. The patellar tendon window injury model used in the present study is not representative of tendon ruptures observed clinically that are commonly presented with degenerative changes.…”
Section: Limitations Of This Studymentioning
confidence: 70%
“…Moreover, since the IdU label was lost during cell proliferation, it could only be used to trace the early events after tissue injury. The use of other tendon stem cell tracking methods should be considered if investigators are interested in the mid-to-late events after injury [45]. The patellar tendon window injury model used in the present study is not representative of tendon ruptures observed clinically that are commonly presented with degenerative changes.…”
Section: Limitations Of This Studymentioning
confidence: 70%
“…214217 When TDSCs were isolated and implanted as TDSC-fibrin glue constructs into patellar tendon defects using a rat model, 218 the collagen content, fiber orientation, and biomechanical properties were significantly improved in the TDSC-group relative to fibrin only controls at four weeks post-injury. Pietschmann et al 219 created rat Achilles tendon defects which were bridged by PGA and collagen type I scaffolds seeded with either tail tendon-derived cells or BMSCs.…”
Section: Use Of Mesenchymal Stem Cells For Tendon Healingmentioning
confidence: 99%
“…Niche components that likely regulate TSPCs include the extracellular matrix, soluble factors, and the surrounding mechanical forces. 29 It has been reported that TSPCs reside within a unique niche, where two extracellular matrix proteins, biglycan and fibromodulin, regulate their function by modulating BMP and Wnt3a signaling. 3 BMP-2 has been shown to promote non-tenocyte differentiation and proteoglycan deposition of TDSCs in vitro 38; 39 while Wnt3a is known to promote the osteogenic differentiation of TDSCs in vitro.…”
Section: Tendon Stem/progenitor Cells (Tspcs) and Induced Pluripotmentioning
confidence: 99%